2019
DOI: 10.1177/0731948719837912
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Rates of Students Identified for Special Education and Their Interstate Variability: A Longitudinal Approach

Abstract: We investigated the variability across states in the prevalence of learning disabilities (LD) as reported by the U. S. Department of Education’s Office of Special Education Programs (OSEP). This expanded upon the work of Hallahan and colleagues on interstate prevalence rate variability of special education disability categories by focusing on a longitudinal analysis. Furthermore, we examined the effect of response to intervention (RTI) on the change in identification of LD more than 12 years from Fall 2000 thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…However, the present findings also differ from Pullen et al (2020) in terms of the prevalence rates observed. The national data reviewed by (Pullen et al, 2020). indicated a lower SLD and higher LI prevalence rate than the Florida data suggest.…”
Section: Comparison To Prior Researchcontrasting
confidence: 99%
See 4 more Smart Citations
“…However, the present findings also differ from Pullen et al (2020) in terms of the prevalence rates observed. The national data reviewed by (Pullen et al, 2020). indicated a lower SLD and higher LI prevalence rate than the Florida data suggest.…”
Section: Comparison To Prior Researchcontrasting
confidence: 99%
“…Finally, the present findings in part confirmed the findings of Pullen et al (2020), with significant decreases in SLD prevalence over the time examined. However, the present findings also differ from Pullen et al (2020) in terms of the prevalence rates observed. The national data reviewed by (Pullen et al, 2020).…”
Section: Comparison To Prior Researchsupporting
confidence: 89%
See 3 more Smart Citations